Adaptive vibration control method for double‐crystal monochromator base on VMD and FxNLMS. (20th February 2023) - Bai, Yang; Gong, Xuepeng; Lu, Qipeng; Song, Yuan; Zhu, Wanqian; Xue, Song; Wang, Dazhuang; Peng, Zhongqi; Zhang, Zhen
Abstract : With the performance of synchrotron radiation sources increasing significantly, higher requirements have been placed on the stability of double‐crystal monochromators (DCMs). Using traditional passive vibration control techniques, such as optimized structures, elastic damping and vibration‐absorbing materials, is unlikely to meet the future requirements of DCMs. The proposed method is the first attempt of an adaptive filtering algorithm based on variational modal decomposition in the field of DCMs development, which is an advancement for the development of high‐performance DCMs at synchrotron radiation facilities. Abstract : Double‐crystal monochromators (DCMs) are one of the most critical optical devices in beamlines at synchrotron sources, directly affecting the quality of the beam energy and position. As the performance of synchrotron light sources continues to improve, higher demands are placed on the stability of DCMs. This paper proposes a novel adaptive vibration control method combining variational modal decomposition (VMD) and filter‐x normalized least mean squares (FxNLMS), ensuring DCM stability under random engineering disturbance. Firstly, the sample entropy of the vibration signal is selected as the fitness function, and the number of modal components k and the penalty factor α are optimized by a genetic algorithm. Subsequently, the vibration signal is decomposed into band frequencies that do not overlap with each other. Eventually, each band signal is individually governed by the FxNLMS controller. Numerical results have demonstrated that the proposed adaptive vibration control method has high convergence accuracy and excellent vibration suppression performance. Furthermore, the effectiveness of the vibration control method has been verified with actual measured vibration signals of the DCM.